2013
DOI: 10.1016/j.jadohealth.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Sexting, Substance Use, and Sexual Risk Behavior in Young Adults

Abstract: Purpose Cell phone use has become more widespread over the past decade. Young adults are frequently early adopters of new technologies, including cell phones. Most prior research examining sexting, the act of sending sexually explicit or suggestive images via text message, has focused on the legal or social consequences of this behavior. The current study focused on the public health implications of sexting by examining associations between sexting, substance use, and sexual risk behavior in youth. Methods Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
198
8
31

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(256 citation statements)
references
References 22 publications
19
198
8
31
Order By: Relevance
“…This result is supported by the study of Currin et al (2016) where condomless sex was also not associated with sexting behaviors. However, the result was in contrast to findings by Benotsch et al (2013) and Crimmins & Seigfried-Spellar (2014) which had confirmed a relationship between sexting and unprotected sex. More in-depth research is required to explore whether and how sexting leads to unprotected sex or vice versa.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This result is supported by the study of Currin et al (2016) where condomless sex was also not associated with sexting behaviors. However, the result was in contrast to findings by Benotsch et al (2013) and Crimmins & Seigfried-Spellar (2014) which had confirmed a relationship between sexting and unprotected sex. More in-depth research is required to explore whether and how sexting leads to unprotected sex or vice versa.…”
Section: Discussioncontrasting
confidence: 99%
“…An increase in the frequency of sexting was associated with an increase in the number of sexual partners. This is similar to findings by Benotsch et al (2013). Multiple sexual partners make young people probably more likely to receive and send sexts more often than having only one or no sexual partner.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…O consumo de bebidas alcoólicas em estudantes universitários é uma das variáveis mais estudadas nesta população, visto que, além de problemas relacionados a ocorrência de doenças, este comportamento está associado a diversos outros riscos, como prática sexual não segura e direção imprudente 19 . No presente estudo, houve aumento do consumo entre os homens e o tempo de exposição ao ambiente da graduação explicou a variância em 13,0% e 14,0% (consumo excessivo) do consumo de bebidas alcoólicas.…”
Section: Discussionunclassified